Crystal structures and polymorphism of polymers: Influence of defects and disorder. Issue 4 (27th August 2018) - De Rosa, Claudio; Auriemma, Finizia; Malafronte, Anna; Scoti, Miriam
Abstract: The crystal structures and the polymorphism of polymers are described on the basis of the main principles that define the conformation of polymer chains in the crystalline state and the modes of packing of macromolecules. We show that the presence of defects and disorder in the crystals influences the polymorphic behavior. The cases of polymorphism of isotactic poly(butene) (iPB) and syndiotactic poly(styrene) (sPS) are ilustrated as examples. In the case of iPB, the effect of the presence of defects of stereoregularity and of comonomeric units on the crystallization of form I and form II is described as an example of alteration of the crystallization behavior because of the modification of both thermodynamic stability and crystallization kinetics from the melt of the polymorphic forms. The case of sPS is taken as an example of a very complex polymorphic behavior arising from the presence and development of structural disorder. Abstract : Polymers present, generally, complex polymorphic behavior. Polymorphism is affected by the presence of defects in the molecular structure and often arises from crystallization of disordered structures. The structural disorder present in polymer crystals is not a defect of the structure but may be described as a structural feature. The disorder and the regular packing of a structural motif produce a similar structure, for example, in isotactic and syndiotactic polystyrenes.